2009
DOI: 10.1590/s0101-31222009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças estruturais entre tegumentos de sementes de soja com permeabilidade contrastante

Abstract: RESUMO -A exposição das sementes de soja a ciclos alternados de elevada e baixa umidades antes da colheita, provocado pela ocorrência de chuvas freqüentes, orvalho ou às flutuações diárias da umidade relativa do ar, resulta na deterioração por umidade, a qual pode ser apontada como a principal causa para a baixa qualidade das sementes. Alguns trabalhos têm evidenciado a existência de genótipos de soja contrastantes para qualidade fisiológica de sementes. Tais diferenças podem existir em virtude da total ou par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 5 publications
1
21
0
6
Order By: Relevance
“…These results are in accordance with those observed by Table 1a -Summary of the variance analysis of variables analyzed in the seeds of four contrasting soybean genotypes for coat characteristics SV -Source of variation; Gen. -Genotypes; DF -Degree of Freedom; ns -no significance; *significant to 1% probability; TKW -Thousand weight seeds; G -germination; FC -first count; SH -shoot height; RL -Root length; TH -Total seedling height; G¹; FC¹ -same meaning as previous acronyms, however, with prior seed immersion in water for 24 hours Mertz et al (2009), which also found no difference in the germination test for the black TP cultivar and the CD202 cultivar with yellow coat.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are in accordance with those observed by Table 1a -Summary of the variance analysis of variables analyzed in the seeds of four contrasting soybean genotypes for coat characteristics SV -Source of variation; Gen. -Genotypes; DF -Degree of Freedom; ns -no significance; *significant to 1% probability; TKW -Thousand weight seeds; G -germination; FC -first count; SH -shoot height; RL -Root length; TH -Total seedling height; G¹; FC¹ -same meaning as previous acronyms, however, with prior seed immersion in water for 24 hours Mertz et al (2009), which also found no difference in the germination test for the black TP cultivar and the CD202 cultivar with yellow coat.…”
Section: Resultsmentioning
confidence: 99%
“…This genotype is considered more susceptible to deterioration as a result of moisture and mechanical damage, precisely because of the lower resistance of its coat due to a lower concentration of lignin (BAHRY et al, 2015;MERTZ et al, 2009). This as well may lead to less control over the entry of water in the initial stage of seed soaking, not allowing an adequate reorganization of the membrane system, causing irreversible damage to the embryo and, consequentially, reducing the number of normal seedlings (ZIMMER, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations